Birds of Ban-ban, Central Negros, Philippines: Threats and Conservation Status - Pagunutalan, Lisa Marie J.; Gonzales, Juan Carlos T.; Gadiana, Mery Jean C.; Dans, Andres Tomas L.; Pedegrosa, Marisol G.; Cariño, Apolinario; Dolino, Cynthia N. (Silliman Journal, 2022)
The forest in Ban-ban, Ayungon, Negros Oriental. Philippines, was surveyed in March to April 1999. Some 4,956 ha of extensive mature secondary forest reported in 1991 were severely reduced to mere 1,559 ha in 1999. Five of the 18 threatened species of Negros and two near-threatened species were confirmed to be present. A significant population of the Visayan Tarictic Hornbill: Penelopides panini (not recorded in 1991) was discovered. Rufous-lured Kingfisher (Halcyon winchelli), believed locally extinct on Negros, was found to be present but rare in the area. Two species of owl, Philippine Hawk Owl Ninox philippensis centralis and the distinct Philippine Scops Owl Otus megalotis nigrorum, were netted. In 1991, six individuals of White-throated Jungle Flycatcher (Rhinomyias albigularis) was observed, but during this survey the team managed to see only two individuals of Rhinomyias species. Mining, quarrying activities, and the local development of the area have increasingly devastated and divided the forest block into smaller and smaller fragments. A number of trees were observed ringed and poisoned. An assessment of long-term conservation needs of the area is long overdue. Immediate conservation action is needed for the preservation of the forest and its wildlife inhabitants.